A Trait-Based Approach to Self-Organized Pattern Formation in Ecology - Dong, Xiaoli (Frontiers in Ecology and Evolution, 2020)
Significant effort in the study of self-organized pattern formation has focused on the physical conditions of the ecosystem. But what about the organisms involved? Can just any species form patterns or are certain traits required? I performed a metadata analysis of pattern-forming species in various patterned ecosystems worldwide and analyzed trait values and other biological characteristics to address this question. Results indicate that some species are more likely to form patterns than others, as a result of their possessing a portfolio of traits conducive to pattern formation. There is a conservation of these traits among species forming vegetation patterns across regions of the world. The degree of conservation is high when regular patterns are formed by the mechanism of scale dependent feedbacks. In contrast, when regular patterns arise from interspecific competition, cross-site variation among pattern-forming species becomes high. Understanding evolutionary implications of pattern formation can be enhanced by this trait-based approach, a perspective that has been lacking to date.